Building Secure and Reliable Systems - Adkins, Heather; Beyer, Betsy; Blankinship, Paul; Lewandowski, Piotr; Oprea, Ana; Stubblefield, Adam (O'Reilly Media, Inc., 2020)
Can a system ever truly be considered reliable if it isn't fundamentally secure? In two previous O'Reilly books, experts from Google showed how reliability is fundamental to service design. Site Reliability Engineering and The Site Reliability Workbook demonstrated how and why a commitment to the entire service lifecycle enables organizations to successfully build, deploy, monitor, and maintain software systems. Security is also crucial to the design and operation of scalable systems in production, as it plays an important part in product quality, performance, reliability, and availability. In a world where most products are connected to the internet, and with cloud technologies and machine learning becoming more prevalent, enabling security by default is increasingly important. This book shares best practices to help an organization of any size design scalable and reliable systems that are fundamentally secure. It also offers insights into how teams across an organization can collaborate on security and reliability. Specifically, you'll learn about: Design Strategies Implementation and Operations Preparing for the Worst: Detection and Response Scaling Security and the Organization.
Online resource; Title from title page (viewed March 25, 2020)